PENGARUH EXPERIENTIAL MARKETING DAN AKSESBILITAS TERHADAP MINAT KUNJUNG ULANG (STUDI KASUSPENGARUH EXPERIENTIAL MARKETING DAN AKSESBILITAS TERHADAP MINAT KUNJUNG ULANG (STUDI KASUS WISATA GREEN HILL SIRAMPOG) - Baehaqi, Imam; Yulianto, Andi; Setiadi, Roby; Iskandar, Khalid (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of experiential marketing and accessibility on interest in repeat visits. The method used in data collection is by observing and distributing online questionnaires to tourists who have visited Green Hill tourism at least once. And the data obtained will be processed using statistical data analysis applications or processed with SPSS. The results of this study state that the experiential marketing and accessibility variables have a significant effect on the variable of interest in revisiting this can be seen from the results of the T test on the experiential marketing variable that is equal to t count 5,829 > t table 2,364 and the accessibility variable also has a significant effect on interest re-visit that is equal to t count 4.162 > t table 2.364.